Optimum calculation of tilt angles and components of standalone photovoltaic system to harvest solar energy - Ahmed, Ameen Sarhan Abdullah (2018)
Recently, there has been renewed interest in PV system worldwide because of high demand for green energy resources as an alternative to conventional energy resources, which contribute to the enormous amount of greenhouse gasses and a resultant global warming in the earth atmosphere. In under developing countries, there is a sharp shortage in electricity supply, PV system may prove to be adequate solution for supplying the required electrical load in such counties. However, the drawback of PV system is the high capital cost as compared to conventional energy sources. For lower energy cost and better performance, the components of PV system and its tilt angle must be designed optimally. Yemen is under developing country suffering from shortage of electricity especially in remote areas. Nevertheless, Yemen receives abundant sunshine all year round, thereby making solar energy a promising alternative to conventional fuels. Moreover, there are many isolated and remote areas located far away from the national electrical grid and require a large fund to be integrated in the near future. Therefore, Standalone Photovoltaic (SAPV) system is an adequate solution for electrification in such area. However, one of the main obstacles of PV system compared to conventional energy sources is the initial high capital cost. So, for low-energy cost and enhanced performance, the size of the systemâAZs components, as well as PV array tilt angle, need to be designed optimally.This study aims to optimize the annual, bi-annual, quarterly, and monthly tilt angles of PV panels for various cities in Yemen based on the model of Liu and Jordan for solar radiation on inclined surfaces. Moreover, an improved optimization method for sizing and configuration standalone photovoltaic (PV) systems is presented. For simulation purpose, 22-year monthly average horizontal and diffused solar radiation and ground albedo data were obtained from NASA, and MATLAB software was utilized to optimize the tilt angle by maximizing the solar radiation on the PV panel. Optimization and configuration algorithm of sizing SAPV system is implemented using MATLAB and hourly meteorological data and load demand. Loss of load probability analysis is conducted to set the benchmark for determining all possible PV arrays and battery capacities. Then, the optimum design is proposed based on the lowest levelized cost of energy (LCE) and net present value (NPV ). Consequently, by applying the annual, bi-annual, quarterly, and monthly optimum tilt angles, the collected gain of the PV module increases by 2.86%, 8.52%, 8.61%, and 9.30%, respectively. Based on the calculated results, the tilt angle should be changed at least twice a year for improving the productivity of PV systems in Yemen and nearby countries. Regarding the 2.475 kWp PV system, the results show that the net present value of the PV system for Yemen is 22224 USD, while the cost of energy generated by the proposed system is 0.403 USD/kWh at Loss of Load Probability (LLP) equal to 0.130%.